2021
DOI: 10.3390/antibiotics10101164
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa mexR and mexEF Antibiotic Efflux Pump Variants Exhibit Increased Virulence

Abstract: Antibiotic-resistant Pseudomonas aeruginosa infections are the primary cause of mortality in people with cystic fibrosis (CF). Yet, it has only recently become appreciated that resistance mutations can also increase P. aeruginosa virulence, even in the absence of antibiotics. Moreover, the mechanisms by which resistance mutations increase virulence are poorly understood. In this study we tested the hypothesis that mutations affecting efflux pumps can directly increase P. aeruginosa virulence. Using genetics, p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…3 ). Supporting this conclusion, notwithstanding some exceptions ( 82 ), it has been described that MexCD-OprJ and MexEF-OprN upregulation entails a reduction in P. aeruginosa virulence ( 41 , 83 , 84 ), due, at least in part, to the implication of these efflux systems in P. aeruginosa ’s quorum sensing response ( 85 , 86 ). Nevertheless, we are aware that other mutations, not analyzed in the current work, may also contribute to these effects on virulence.…”
Section: Discussionmentioning
confidence: 81%
“…3 ). Supporting this conclusion, notwithstanding some exceptions ( 82 ), it has been described that MexCD-OprJ and MexEF-OprN upregulation entails a reduction in P. aeruginosa virulence ( 41 , 83 , 84 ), due, at least in part, to the implication of these efflux systems in P. aeruginosa ’s quorum sensing response ( 85 , 86 ). Nevertheless, we are aware that other mutations, not analyzed in the current work, may also contribute to these effects on virulence.…”
Section: Discussionmentioning
confidence: 81%
“…are indicators of increased pathogenicity in the host in cystic fibrosis (CF) patients ( 49 , 50 ). Further, the mexEF-oprN efflux pump is known to increase virulence in various conditions including CF ( 51 , 52 ). Our study suggests that the mexEF-oprN efflux pump is specific for GlcNAc, Cu, Fe, and Zn.…”
Section: Resultsmentioning
confidence: 99%
“…The product of this gene is functionally similar to the MexB-AcrB efflux pump, which confers resistance to β-lactams and cationic antimicrobial peptides. Poole et al (1993) previously reported that deleting the genes encoding the MexAB-OprM efflux pathway in Pseudomonas aeruginosa resulted in hypersensitivity to many antimicrobial compounds [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%